2019
DOI: 10.4155/bio-2019-0090
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Occupancy Measurement of Anti-PD-1 Antibody Drugs in Support of Clinical Trials

Abstract: Aim: The reliable measurement of receptor occupancy (RO) provides informative data for efficacy and safety evaluation. This study aimed to assess factors affecting RO measurement of anti-PD-1 antibodies in clinical studies. Materials & methods: RO performance was assessed using different T-cell activation markers measured by flow cytometry. The validated methodology was then used in support of a clinical study. Results: The optimized active cell population was comprised of CD45RO+ or CD45RA− T cells. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Downmodulation of PD-1 expression by ~25% in cancer patients during the treatment with anti-PD-1 mAbs has been reported. 16 , 18 The PD-1 pathway has a sophisticated system of recycling that rescue internalized receptor from degradation and maintain surface receptors at a certain level. 19 Hence, the use of equation 3 allows dynamic changes in the number of bound receptors normalized to the baseline to be monitored: if PD-1 receptors are completely occupied by an antibody that induces receptor internalization, decreasing expression below the baseline level (Figure S5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downmodulation of PD-1 expression by ~25% in cancer patients during the treatment with anti-PD-1 mAbs has been reported. 16 , 18 The PD-1 pathway has a sophisticated system of recycling that rescue internalized receptor from degradation and maintain surface receptors at a certain level. 19 Hence, the use of equation 3 allows dynamic changes in the number of bound receptors normalized to the baseline to be monitored: if PD-1 receptors are completely occupied by an antibody that induces receptor internalization, decreasing expression below the baseline level (Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“… 31 The internalization rate of bound PD-1 should be substantially higher than the degradation rate that results in the apparent receptor downmodulation (median fold change ~0.75) during the course of treatment with anti-PD-1 mAbs. 16 , 18 All these processes occur at the cellular membrane, the surface area of which was estimated based on the spherical volume of cell. 32 The full list of parameters related to the PD-1 receptor is presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…With regards to achieving sufficient therapeutic concentrations, multiple dose-range finding studies have investigated optimal CPI dosing [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Both preclinical models and clinical trials have demonstrated that there is no meaningful increase in efficacy between doses with over 100-fold differences and that lower doses already saturate the majority of the relevant receptors up to 100% [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The data indicate that lower doses may be equally as effective, especially when targeted appropriately using techniques such as RD.…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies target programmed cell death protein 1 (PD‐1) on the surface of antigen‐specific dysfunctional (“exhausted”) T cells [ 11 ] by binding to defined PD‐1 extracellular epitopes [ 12 ]. In addition, several other anti‐PD‐1 therapeutic mAbs are in clinical development or already approved [ 10 , 13 , 14 , 15 ], highlighting the importance of this molecule for CIT. In the case of the clinical development of CPIs, some trials included RO by flow cytometry to confirm the degree of PD‐1 occupancy in patients and establish pharmacokinetics–pharmacodynamics (PK–PD) relationships.…”
Section: Introductionmentioning
confidence: 99%